A Dual-Platform Point-of-Care Test for Neurosyphilis Diagnosis. Issue 5 (May 2021) - Gonzalez, Hemil; Koralnik, Igor Jerome; Huhn, Gregory D.; Tantalo, Lauren C.; Ritz, Ethan M.; Orban, Zachary; Marra, Christina M.
Abstract : Background: The diagnosis of neurosyphilis relies on cerebrospinal fluid (CSF) abnormalities (pleocytosis, elevated protein) and CSF–Venereal Disease Research Laboratory (VDRL) test. In resource-limited settings, the CSF-VDRL test may not be widely available. Methods: We optimized a commercial immunochromatographic strip test, the DPP Chembio syphilis assay, for performance with CSF and tested centrifuged CSF samples of 71 patients with syphilis (35 with neurosyphilis and 36 without neurosyphilis). A CSF dilution of 1:4 was chosen based on agreement with CSF pools with documented results from the CSF-VDRL test and fluorescent treponemal antibody absorption test on CSF. Using an electronic reader, we obtained unit values of treponemal and nontreponemal antibodies for all study samples and generated a receiver operating characteristic curve; using the Youden index, we established diagnostic cutoffs with optimal sensitivity and specificity. Results: Diagnostic sensitivity of the nontreponemal test was 80% (95% confidence interval, 63%–92%) and specificity was 97% (95% confidence interval, 85%–100%) for neurosyphilis diagnosis using a reactive CSF-VDRL that improved after neurosyphilis therapy as a criterion standard. Conclusions: In this small study, the DPP Chembio test showed promising results for neurosyphilis diagnosis. Further studies are needed to assess its performance in resource-limited settings. Abstract : We optimized the DPP Chembio syphilis assay on cerebrospinal fluid for the diagnosis of neurosyphilis and found that this point-of-care test has a diagnostic performance that is similar to a clinicoserological definition of neurosyphilis.Supplemental digital content is available in the text.